DECRETUL NR. 177 DIN 1948 ȘI LIBERTATEA CULTELOR RELIGIOASE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Decree No 177 of 1948 and freedom of religious cult.In writing this study on „Decree No 177 of 4 August 1948 for the general regime of religious cults”, drawn up on the basis of the provisions of principle of the Constitution of the Romanian People’s Republic promulgated on 13 April 1948, I have taken into account two indispensable realities, namely: a) the fact that few of the Romanian theologians, jurists, sociologists, political scientists and historians - who have commented on its content - have had an interdisciplinary training that would allow them to examine and evaluate it through such an approach; b) the fact that some provisions of the text of this Decree-Law - to which some amendments were made after 1990, imposed by the socio- political guidelines and realities of the post-december epoch - were in force until 2006, when a new Law on Religious Cults was promulgated, namely Law no. 489 of 2006. Taking these two realities into account, through the text of this study we have been able to bring to the reader’s attention some clarifications and precisions of juridical and canonical doctrine that could be of real help for a better understanding of the text of the provisions of this Decree. Unfortunately, by some of its statements, Decree no. 177 of 1948 has survived in the text of Law no. 489 of 2006, although some of them, such as article 7, should have been taken over in their entirety, since the new law provides that the religious establishments are organized „according to their own ... canonical codes” (Art. 14 para. 2 Law no. 489/2006), and not according to „their canons and traditions”, as provided in article 7 of Decree no. 177 of 4 August 1948.